Neural search - from prototype to production with Jina : learn how to build deep-learning-powered search systems that you can deploy and manage with ease /: learn how to build deep-learning-powered search systems that you can deploy and manage with ease. (2022) - Guzman, Susana; Wang, Bo; Mitroi, Cristian; Wang, Feng; Saboo, Shubham
No abstract available